Syntheses of two deacetyl-thymosin α1 analogues and their effects on low E-rosette-forming lymphocytes of uraemic patients - T. Abiko; H. Sekino (Mediators of Inflammation)
Two deacetyl-thymosin α1 analogues containing Phe (4Br) or D-Phe (4Br) residue—[D-Phe(4Br)21]deacetyl-thymosin α1 and [Phe(4Br)21]deacetyl-thymosin α1, respectively—were synthesized by the manual solid-phase method and their immunological effects on the low E-rosette-forming lymphocytes of uraemic patients were examined. One of the synthetic analogues, [Phe(4Br)21deacetyl-thymosin α1, demonstrated a restorative effect on the low E-rosette-forming lymphocytes of uraemic patients, which was stronger than that of deacetyl-thymosin α1, but the other analogue, [D-Phe(4Br)21]deacetyl-thymosin α1, showed no restorative effect under the same conditions.